Weak formulation of singular differential expressions in spaces of functions with minimal derivatives - M. A. El-Gebeily (Abstract and Applied Analysis)
A weak formulation for singular symmetric differential expressions is presented in spaces of functions which possess minimal differentiability requirements. These spaces are used to characterize the domains of the various operators associated with such expressions. In particular, domains of self-adjoint differential operators are characterized.